Determination of operating conditions of box culverts with different technical specifications - Kok, Baha Vural; Yetkin, Zulfu; Yalcin, Erkut; Ozdemir, Ahmet Munir (Pamukkale Univ, 2026)
As a result of improper planning of culvert structures constructed for the passage of water flowing in stream beds to the other side of the road body, the road may become unserviceable and access to the areas that need to be reached, especially in disaster situations, is interrupted, causing significant material and moral damages. In this study, the performance of the most commonly used box culverts on highways is analyzed within the framework of technical parameters. The effects of culvert slope, roughness, length and different culvert inlet types on inlet water height and outlet water velocity were investigated. It was found that outlet-controlled conditions prevail when the culvert slope is low and roughness is increased, slope, roughness and length have a significant effect on the outlet water velocity, and the best performance is obtained when the culvert inlet is inclined at33.7 degrees, the culvert inlet is tapered by 50% and the wing wall is 27 degrees.
Keywords: Box culvert; flood; operating conditions; optimum design; HY-8